Antenatal AVSD diagnosis at Groote Schuur Hospital A retrospective cohort study - Annor, Charlene Adjoa Adobea (Department of Obstetrics and Gynaecology, 2020)
The antenatal diagnosis of a fetal atrioventricular septal defect (AVSD) impacts the prognosis of an unborn child, and may have psychosocial and financial implications for mothers receiving this diagnosis. Outcomes relevant to our local population may be used to improve counselling for parents receiving this diagnosis. During a literature review, there was a lack of existing published data on antenatal AVSD outcomes from the developing world. To ascertain the outcomes of antenatal AVSD diagnosis in fetal, neonatal and infant life, we performed a retrospective study of all AVSD's diagnosed at a tertiary referral hospital in Cape Town (Groote Schuur Hospital) between 1 January 2010 and 31 December 2016. We examined ultrasound records and case folders from the antenatal, neonatal and infancy periods, up to a year of life or demise. The resultant cohort had a total of 55 cases. We found that fetal outcomes in Cape Town, South Africa are similar to those in developed countries. Pregnancies were terminated in just over a third of cases and similarly, the over-all survival to one year of life excluding termination of pregnancy was 29,73%. The bulk of these fetuses demised in the antenatal period, and the rate of demise positively correlated with the presence of associated organ abnormalities and aneuploidies. In those born alive, the correlation between an antenatal AVSD diagnosis and the same diagnosis during postnatal echocardiography was 59,09%, with the remaining 40,91% having other complex cardiac abnormalities diagnosed. Corrective cardiac surgery in the neonatal period or infancy occurred in 46,15% of those born alive, with good outcomes. This study shows similarity between survival of fetuses diagnosed with antenatal AVSD in the developing and developed world. It will be instrumental in appropriately counselling South African parents who receive the diagnosis. In order to assess if prenatal AVSD diagnosis improves neonatal and infant outcomes, a further study comparing this group to the outcomes of infants with postnatally diagnosed AVSD is necessary. More research is needed in an African context regarding the outcomes of babies diagnosed with antenatal anomalies.